Ecotoxicological evaluation of foundry sands and cosmetic sludges using new earthworm biomarkers - Curieses, Silvana Patricia (2016)
The management and final disposal of industrial wastes are a matter of considerable human concern. The present study evaluates the cyto/genotoxic effects and changes of the coelomic cell formulas exerted by aqueous leachates and solid waste (SW) of two industrial residues using coelomocytes extruded from Eisenia fetida. The assayed wastes corresponded to industrial foundry and cosmetic activities. After 14 days of exposure, we obtained a group of endpoints that reflect the toxicity/genotoxicity, coelomocyte formula and indexes; and the mortality classical value (LC50-14d). Among the variables measured, total coelomocytes formula (eleocytes + amebocytes + granulocytes) appears as a single and easy parameter to assess the toxicity of eluates at short exposure times. We applied a set of assays using earthworms as test organism that would allow evaluating SW as well as its aqueous leachates. It is easy to run trials combining exposures of 1 h to 14 days, which can be integrated into the implementation of the traditional test for evaluating acute toxicity.